Aspirin exacerbated respiratory disease - Corrigan, Chris (Henry Stewart Talks, 2012)
Clinical features, AERD as a disease of excessive leukotriene production, Alterations in eicosanoid metabolism, The protective role of Prostaglandin E2 (PGE2), Reduced PGE2 signalling as a mechanism for AERD, The PGE2 receptor EP2 as a molecular target
Reviewed at 2022/04/12